Perlindungan Hukum Pekerja Tetap atas Pemutusan Hubungan Kerja Akibat Pemisahan Perseroan (Spin Off) ditinjau dari Peraturan Pemerintah Nomor 35 Tahun 2021 - Kevin Darmawan; Holyness N. Singadimedja; Rafan Darodjat (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Labor law in Indonesia prioritizes the protection of workers as a primary focus in industrial relations. This protection becomes highly relevant in the context of termination of employment (PHK), particularly in cases where PHK is carried out on the grounds of corporate spin offs. This study aims to analyze the company’s responsibility in fulfilling workers' rights and the legal measures that can be taken to ensure workers' welfare in accordance with Government Regulation No. 35 of 2021. The research method employs a normative juridical approach with descriptive-analytical review of primary documents, such as labor-related legislation, and secondary documents related to the PHK process. The analysis reveals that PHK conducted by a company on the basis of a spin off lacks a strong legal foundation if it contradicts the principles of legal certainty and worker protection as stipulated in applicable regulations. In the event that PHK is still carried out, the company is obligated to provide full compensation to workers, including severance pay, service appreciation pay, and rights replacement as outlined in PP 35/2021. Furthermore, workers are advised to pursue their rights through non-litigation, litigation at the Industrial Relations Court, or administrative measures in a step-by-step manner. The implication of these findings underscores the importance of enforcing labor laws to protect workers' rights during corporate restructuring.